PENGARUH LABA AKUNTANSI, TINGKAT HUTANG, DAN ARUS KAS OPERASI TERHADAP DIVIDEN TUNAI (STUDI KASUS PADA PERUSAHAAN REAL ESTATE DAN PROPERTI) YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Pratami, Alya Fitri; Asak, Putu Rani Adnyani; Iswandir, Iswandir (JURNAL MITRA MANAJEMEN, 2025)
The purpose of this research is to determine effect of accounting income, laverage, and operating cash flows on cash dividen of the real estate and property companies listed in Indonesia Stock Exchange period 2016-2020.  The research uses causal research design with the population of real estate and property companies listed in the Indonesia Stock Exchange period 2016-2020. This research uses purposive sampling method with the number of sampole of 6 which is a real estate and property companies listed in tne Indonesia Stock Exchange period 2016-2020. The data collection process in this resesarch was carried out using secondary data, that is financial report of real estate and property companies’ period 2016-2020 at Indonesia Stock Exchange.  The results of the partially research show that accounting income have an effect on cash divident, while laverage does not have an effect on cash divident, and the operating cash flows does not have an effect on cash divident. The results of the simultaneous research show that accounting income, laverage, and operating cash flows have significant positive to cash divident in real estate and property companies listed in the Indonesia Stock Exchange periode 2016-2020.   Keywords: Accounting Income, Laverage, Operating Cash Flows, Cash Dividen